Materials development program for in-service teachers localizing Waray mother tongue learner's materials for Ninorte-Samarnon speakers - Merino, Phoebe Maria Blanca S.
Linguistic diversity of the Philippines has posed a challenge to the development of learning materials (LMs) for the country's MTB-MLE implementation. According to studies, these challenges include: lack of LMs written in the mother tongue (MT), mismatch of the language used in the LM with the actual MT of the learners, and lack of teacher training on materials development. This study aims to recommend protocols and formats in designing professional development programs in localizing MT LMs and provide localized MT LMs for the teachers and learners through implementing a proposed localization program in localizing Waray MT LMs for Ninorte-Samarnon speakers. The 5-day localization program was participated by an average of 49 teachers from a school district in Northern Samar. The localization program was the medium from which the following were drawn: l) characteristics of an effective professional development program exemplified in the localization program; 2) materials writing skills developed among teacher-participants in the localization program; and 3) qualities of a good localized MT LM manifested in the materials developed by teacher-participants. To identify the abovementioned, teacher-participants evaluated the program evaluation through an overall program (OProg) evaluation questionnaire which also included a self-evaluation on the teacher-participants' materials writing skills before and after the implementation of the localization program was conducted. The localized MT LMs, presented as output of the teacher-participants, were evaluated by a panel of experts. Quantitative data were analyzed by interpreting the weighted mean (WM) using the indicated scale in the tools. On the other hand, reductive coding was used to analyze qualitative data. The results showed that the localization program manifested all characteristics of effective professional development program suggested by a "very satisfactory" rating. These characteristics are: l) delivers rich and relevant content (WM = 3.90); 2) focuses on localization of materials (WM = 3.92); 3) equips participants with materials writing skills in localizing materials (WM = 3.90); 4) exercises appropriate professional development practices (WM = 3.95); 5) instills positive attitude towards the localization program (WM = 3.96); 6) involves competent speakers and presenters (WM=3.96); and 7) provides conducive learning environment OVM = 3.78). It was also found out that there is a statistically significant improvement (t=15.84; p<0.05) in all of the teacher participants' materials writing skills in localizing MT LMs. These materials writing skills are: l) identifying language learning needs; 2) writing or adapting original stories in the mother tongue; 3) translating & adapting texts; 4) adopting locally produced materials; 5) selecting or writing interesting and culturally familiar stories, poems, and other texts; 6) using a variety of forms for reading texts; 7) using local vocabulary appropriate to the learners' language learning level; 8) developing language learning exercises that are challenging yet achievable; 9) selecting or creating activities that develop the four macro-skills: reading, writing, speaking, and listening; 10) writing simple and clear instructions; 1 1) drawing illustrations and images; and 12) evaluating and selecting texts, images, and illustrations. The K to 3 LMT LMs, the teacher-participants' outputs, exemplified all qualities of good localized materials as indicated in the overall mean for Kinder (l .86), Grade I (l. 71), Grade 2 (1.77), and Grade 3 (1.82) LMT LMs respectively. These qualities are: l) clear layout and logical organization; 2) appropriate and engaging content; 3) localized text and non-text content; 4) sufficient and challenging tests and tasks; and 5) aligned with DepEd 's goals and pedagogy. Based on these results, this localization program can be used or adapted by other schools and organizations in training teachers in the localization of their LMs. Training teachers to localize their own LMs will help address challenges in the use of MT LMs in linguistically diverse contexts. Most importantly, effective professional development program, such as this study's localization program, trains teachers to not just teach what is on the LM, but also to develop an LM that will help them facilitate their learners' learning process. This study also calls for the conduct of more similar researches on the feasibility of a district-wide localization program to solve challenges on the use of an MT as LOI and its alignment with the actual MT of the learners in regions where dialect continuum exists.